First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Improving long-term storage of liquid-preserved bovine semen: Effect of extender, cooling protocol and holding temperature on sperm quality and fertility - M.L. Neubert; S. Henneberg; A. Riedel; Y. Schulze; M. Hürland; J.H. Osmers; C. Wesenauer; M. Jung; Á.C. Bajcsy; M. Schulze (Theriogenology, 2026)

Short- and long-term impact of aseptic bathing strategies on the skin microbiome in ICU patients - Tilman E. Klassert; Cristina Zubiria-Barrera; Luisa A. Denkel; Mercedes Lopez; Robert Neubert; Amelya Keles Slevogt; Frank Bloos; P. Christian Schulze; Jörg Epstude; Petra Gastmeier; Christine Geffers; Hortense Slevogt (Medical Microbiology and Immunology, 2025)
Bathing strategies with antiseptic agents, such as Chlorhexidine and Octenidine, have been widely adopted to mitigate infection risks in intensive care units (ICU). However, concerns exist regarding their long-term effects on skin microbiome structures and potential unintended consequences, including antibiotic cross-resistance. This longitudinal study characterized the compositional changes of the skin microbiome of ICU patients upon these two antiseptic bathing strategies when compared to standard water and soap bathing. Samples were collected in a three-armed cluster randomized decolonization trial (registration number DRKS00010475). Skin swabs from 5 different sites and three time points were analyzed by culture-based methods, 16S rRNA-gene amplicon sequencing and multiplex Taq-Man assays for detection of antimicrobial resistance genes (ARG). Our results show that Chlorhexidine bathing led to a sustained reduction of the bacterial biomass on different skin sites, as measured by both molecular and culture-based methods. Thereby, the microbial structures remained largely unaltered both in their diversity and their taxonomic composition. However, the loss of microbiome site-specificity observed on the skin of ICU patients remained unchanged independently from the bathing strategy applied and persisted even after discharge. None of the antiseptic bathing strategies led to an increase or accumulation of antibiotic-resistance determinants on any of the skin sites investigated in this study. Thus, this study suggests that daily patient bathing with 2% Chlorhexidine impregnated cloths or 0.08% Octenidine wash mitts does not impact skin microbiome structures and antibiotic resistance gene accumulation in ICU patients when compared to non-antiseptic water and soap bathing routine.

Small Phytoplankton Community Composition Cycles Annually With a Coastal Bloom - Bethany L. F. Stevens; Rebecca J. Gast; Emily E. Peacock; Yogesh A. Girdhar; Michael G. Neubert; Heidi M. Sosik (Environmental Microbiology, 2025)
Small photosynthetic eukaryotes are a productive and dynamic component of marine planktonic communities. Here, we investigate how seasonal changes in the abundance of these primary producers relate to changes in their community composition at a coastal site on the Northeast US Shelf. We present a 9‐year time series of 18S rRNA sequencing data and identify gradual transitions within the pico‐ and nanoplankton community that occur repeatedly over the annual cycle. We compare these compositional changes to concurrent high‐resolution in situ flow cytometry measurements of eukaryotic phytoplankton abundance and division rate. We find that the Chlorophyta contribute a large proportion of the sequences in our samples and drive much of the seasonal variability within the small phytoplankton community. Across the time series, Bathycoccus , Micromonas and Picochlorum are the dominant genera, with the first being present year‐round, while Micromonas bravo and Picochlorum are representative of the summer community. We also find a strong winter Phaeocystis signal which might be leading to flow cytometry measurements of relatively large cells in the early spring. Our results provide fundamental knowledge of the taxonomic composition of the phytoplankton community on the Northeast US Shelf, improving our understanding of the region's diversity and compositional variability over time.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Development and Validation of a Western Blot Method to Quantify Mini-Dystrophin in Human Skeletal Muscle Biopsies - Catherine I. Soderstrom; Jennifer Larsen; Carolina Owen; David Gifondorwa; David Beidler; Florence H. Yong; Patricia Conrad; Hendrik Neubert; Steven A. Moore; Mohamed Hassanein (The AAPS Journal, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative muscular disease affecting roughly one in 5000 males at birth. The disease is often caused by inherited X-linked recessive pathogenic variants in the dystrophin gene, but may also arise from de novo mutations. Disease-causing variants include nonsense, out of frame deletions or duplications that result in loss of dystrophin protein expression. There is currently no cure for DMD and the few treatment options available aim at slowing muscle degradation. New advances in gene therapy and understanding of dystrophin (DYS) expression in other muscular dystrophies have opened new opportunities for treatment. Therefore, reliable methods are needed to monitor dystrophin expression and assess the efficacy of new therapies for muscular dystrophies such as DMD and Becker muscular dystrophy (BMD). Here, we describe the validation of a novel Western blot (WB) method for the quantitation of mini-dystrophin protein in human skeletal muscle tissues that is easy to adopt in most laboratory settings. This WB method was assessed through precision, accuracy, selectivity, dilution linearity, stability, and repeatability. Based on mini-DYS standard performance, the assay has a dynamic range of 0.5–15 ng protein (per 5 µg total protein per lane), precision of 3.3 to 25.5%, and accuracy of − 7.5 to 3.3%. Our stability assessment showed that the protein is stable after 4 F/T cycles, up to 2 h at RT and after 7 months at − 70°C. Furthermore, our WB method was compared to the results from our recently published LC–MS method. Graphical Abstract Workflow for our quantitative WB method to determine mini-dystrophin levels in muscle tissues (created in Biorender.com). Step 1 involves protein extraction from skeletal muscle tissue lysates from control, DMD, or BMD biospecimen. Step 2 measures total protein concentrations. Step 3 involves running gel electrophoresis with wild-type dystrophin (wt-DYS) from muscle tissue extracts alongside mini-dystrophin STD curve and mini-DYS and protein normalization with housekeeping GAPDH.

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

Bioengineering Priorities on a Path to Ending Organ Shortage - Joshua Hunsberger; Josh Neubert; Jason A. Wertheim; Julie Allickson; Anthony Atala (Current Stem Cell Reports, 2016)

Drug Release from ß-Cyclodextrin Complexes and Drug Transfer into Model Membranes Studied by Affinity Capillary Electrophoresis - Kinda A. Darwish; Yahya Mrestani; Hans-Hermann Rüttinger; Reinhard H. H. Neubert (Pharmaceutical Research, 2016)

Center-of-mass corrections for sub-cm-precision laser-ranging targets: Starlette, Stella and LARES - Toshimichi Otsubo; Robert A. Sherwood; Graham M. Appleby; Reinhart Neubert (Journal of Geodesy, 2015)

Managing Protected Areas Under Climate Change: Challenges and Priorities - Sven Rannow; Nicholas A. Macgregor; Juliane Albrecht; Humphrey Q. P. Crick; Michael Förster; Stefan Heiland; Georg Janauer; Mike D. Morecroft; Marco Neubert; Anca Sarbu; Jadwiga Sienkiewicz (Environmental Management, 2014)

Prevalence of antibodies against hepatitis A virus among children and adolescents in Germany - A. Krumbholz; A. Neubert; H. Girschick; H. I. Huppertz; P. Kaiser; J. Liese; A. Streng; T. Niehues; J. Peters; A. Sauerbrey; H. Schroten; T. Tenenbaum; et al. (Medical Microbiology and Immunology, 2013)

A Novel Approach for In Vitro Studies Applying Electrical Fields to Cell Cultures by Transformer-Like Coupling - R. Hess; H. Neubert; A. Seifert; S. Bierbaum; D. A. Hart; D. Scharnweber (Cell Biochemistry and Biophysics, 2012)

Contributions of high- and low-quality patches to a metapopulation with stochastic disturbance - Carly A. Strasser; Michael G. Neubert; Hal Caswell; Christine M. Hunter (Theoretical Ecology, 2012)

Radiocarbon based assessment of soil organic matter contribution to soil respiration in a pine stand of the Campine region, Belgium - Tommaso Chiti; Rolf E. M. Neubert; Ivan A. Janssens; Jorge Curiel Yuste; Carmina Sirignano; Giacomo Certini (Plant and Soil, 2011)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Neuraminidase-deficient Sendai virus HN mutants provide protection from homologous superinfection - Christine A. Baumann; Wolfgang J. Neubert (Archives of Virology, 2010)

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Women encounter ADRs more often than do men - Y. Zopf; C. Rabe; A. Neubert; K. G. Gaßmann; W. Rascher; E. G. Hahn; K. Brune; H. Dormann (European Journal of Clinical Pharmacology, 2008)

Penetration Profile of Taurine in the Human Skin and Its Distribution in Skin Layers - D. L. P. da Silva; S. B. Thiago; F. A. Pessôa; Y. Mrestani; H. H. Rüttinger; J. Wohlrab; R. H. H. Neubert (Pharmaceutical Research, 2008)

Localisation of partially deuterated cholesterol in quaternary SC lipid model membranes: a neutron diffraction study - Doreen Kessner; Mikhail A. Kiselev; Thomas Hauß; Silvia Dante; Siegfried Wartewig; Reinhard H. H. Neubert (European Biophysics Journal, 2008)

Fatty acid interdigitation in stratum corneum model membranes: a neutron diffraction study - A. Ruettinger; M. A. Kiselev; Th. Hauss; S. Dante; A. M. Balagurov; R. H. H. Neubert (European Biophysics Journal, 2008)

Recent Results from Studies of Electric Discharges in the Mesosphere - T. Neubert; M. Rycroft; T. Farges; E. Blanc; O. Chanrion; E. Arnone; A. Odzimek; N. Arnold; C.-F. Enell; E. Turunen; T. Bösinger; Á. Mika; et al. (Surveys in Geophysics, 2008)

Medicines for children licensed by the European Medicines Agency (EMEA): the balance after 10 years - A. Ceci; M. Felisi; P. Baiardi; F. Bonifazi; M. Catapano; C. Giaquinto; A. Nicolosi; M. Sturkenboom; A. Neubert; I. Wong (European Journal of Clinical Pharmacology, 2006)

What can we learn about the lipid vesicle structure from the small-angle neutron scattering experiment? - M. A. Kiselev; E. V. Zemlyanaya; V. K. Aswal; R. H. H. Neubert (European Biophysics Journal, 2006)

New insights into the structure and hydration of a stratum corneum lipid model membrane by neutron diffraction - M. A. Kiselev; N. Y. Ryabova; A. M. Balagurov; S. Dante; T. Hauss; J. Zbytovska; S. Wartewig; R. H. H. Neubert (European Biophysics Journal, 2005)

Investigation of Pharmaceutical Oil/Water Microemulsions by Small-Angle Scattering - Anuj Shukla; Martin Janich; Konstanze Jahn; Annett Krause; Mikael A. Kiselev; Reinhard H. H. Neubert (Pharmaceutical Research, 2002)

Invasion theory and biological control - William F. Fagan; Mark A. Lewis; Michael G. Neubert; P. Van Den Driessche (Ecology Letters, 2002)
Recent advances in the mathematical theory of invasion dynamics have much to offer to biological control. Here we synthesize several results concerning the spatiotemporal dynamics that occur when a biocontrol agent spreads into a population of an invading pest species. We outline conditions under which specialist and generalist predators can influence the density and rate of spatial spread of the pest, including the rather stringent conditions under which a specialist predator can successfully reverse a pest invasion. We next discuss the connections between long distance dispersal and invasive spread, emphasizing the different consequences of fast spreading pests and predators. Recent theory has considered the effects of population stage‐structure on invasion dynamics, and we discuss how population demography affects the biological control of invading pests. Because low population densities generally characterize early stages of an invasion, we discuss the lessons invasion theory teaches concerning the detectability of invasions. Stochasticity and density‐dependent dynamics are common features of many real invasions, influencing both the spatial character (e.g. patchiness) of pest invasions and the success of biocontrol agents. We conclude by outlining theoretical results delineating how stochastic effects and complex dynamics generated by density dependence can facilitate or impede biological pest control.

Identification of theta-class glutathione S-transferase in liver cytosol of the marmoset monkey - Thomas G. Schulz; Frederike A. Wiebel; Ricarda Thier; Diether Neubert; Donald S. Davis; Robert J. Edwards (Archives of Toxicology, 2000)

Partition Behaviour of Drugs in Microemulsions Measured by Electrokinetic Chromatography - Y. Mrestani; R. H. H. Neubert; A. Krause (Pharmaceutical Research, 1998)